C1, α estimates for the parallel refractor. (September 2016) - Abedin, Farhan; Gutiérrez, Cristian E.; Tralli, Giulio
Abstract: We consider the parallel refractor problem when the planar radiating source lies in a medium having higher refractive index than the medium in which the target is located. We prove local C 1, α estimates for parallel refractors under suitable geometric assumptions on the source and target, and under local regularity hypotheses on the target set. We also discuss existence of refractors under energy conservation assumptions.